A Note on Fractional Equations of Volterra Type with Nonlocal Boundary Condition - Zhenhai Liu; Rui Wang (Abstract and Applied Analysis)
We deal with nonlocal boundary value problems of fractional equations of Volterra type involving Riemann-Liouville derivative. Firstly, by defining a weighted norm and using the Banach fixed point theorem, we show the existence and uniqueness of solutions. Then, we obtain the existence of extremal solutions by use of the monotone iterative technique. Finally, an example illustrates the results.